The modification of the new type of end-to-side anastomosis between carotid arteries in rats: A technical and scanning electron microscopic study - (:unkn) unknown (SPRINGER-VERLAG WIEN, 1996)
Modification of a type of end-to-side anastomosis that has been described before is studied. The recipient artery is occluded for only 3-4 minutes to complete the anastomosis by using only the running suture. The anastomotic site was studied by inspection and Scanning Electron Microscope (SEM) at different times after the operation on 30 rats.
Keywords: end-to-side anastomosis; rat; scanning, electron microscopy